2021
DOI: 10.3389/fnut.2020.602090
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inflammatory Potential of the Diet and Ulcerative Colitis: A Case-Control Study

Abstract: Background/Aim: Despite the inflammatory nature of inflammatory bowel disease (IBD), limited data are available on the association of inflammatory potential of the diet and risk of ulcerative colitis (UC). We aimed to investigate the association of inflammatory potential of the diet (IPD) score and odds of UC in a case-control study.Methods: Patients with UC were enrolled from Iranian IBD registry, whose disease was confirmed by a gastroenterologist. Controls were selected randomly from the Study of the Epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They performed a pooled analysis of three large US cohorts, using an empirical dietary inflammatory pattern score, and found a positive association between a pro-inflammatory diet and CD risk (51% higher risk for the highest quartile vs. lowest), but no association with UC [ 17 ], results that are in line with ours. In contrast, two Iranian case-control studies, using the DII or a modified version of it, found a positive association between a more inflammatory diet and the risk of UC [ 18 , 19 ]. However, potential limitations of these studies include the possibility of recall and selection biases, which are inherent in most case-control studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They performed a pooled analysis of three large US cohorts, using an empirical dietary inflammatory pattern score, and found a positive association between a pro-inflammatory diet and CD risk (51% higher risk for the highest quartile vs. lowest), but no association with UC [ 17 ], results that are in line with ours. In contrast, two Iranian case-control studies, using the DII or a modified version of it, found a positive association between a more inflammatory diet and the risk of UC [ 18 , 19 ]. However, potential limitations of these studies include the possibility of recall and selection biases, which are inherent in most case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have specifically evaluated the relation between the overall diet’s inflammatory potential and IBD risk. In a prospective study, a pro-inflammatory diet was related to an increased risk of CD but not UC [ 17 ], while association with UC has been observed in two case-control studies [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…50 Although saturated fat is highly recognized a risk factor for IBD, O'Mahony et al 51 report that a lard-based high-fat diet demonstrates the potential to reduce DSS-induced colitis via inducing high level of the secondary bile acid lithocholic acid and activating the vitamin D pathway. Nevertheless, Khademi et al 52 support that there is no significant link between pro-inflammatory diets containing french fries, pizza, snacks, and red and processed meats with UC risk. There is currently no dietary approach that can be successfully applied to all patients with IBD.…”
Section: Disease Pathogenesismentioning
confidence: 99%